Promoting the use of 'indigenous' scale for the assessment of spoken performance - Abdul Halim Abdul Raof supervisor 300289; Seminar on Teaching and Assessing Language Proficiency (2003 : Singapore) 472621 (Skudai : Universiti Teknologi Malaysia, 2003)
34